Les mathématiques comme habitude de pensée Les idées scientifiques de Pavel Florenski - Betti, Renato (Sciences : concepts et problèmes, 2022)
Russian mathematician, Orthodox priest, deported to the Gulag and dead at the beginning of the XXth century, Paul Florenski conceives mathematics as a human science. His philosophical and mathematical synthesis is grounded on the set theory not only in order to understand the world, but more deeply to even shape phenomena and pin the future spiritual culture for next generation. This approach involves understanding mathematical intuitions as a spiritual form, which enable to perceive directly world in its finitude.